Entrepreneurship: The Value-Added of Co-Creation through Web 3.0 - Vindigni, Giovanni (European Journal of Applied Sciences, 2023)
This paper explores the concept of entrepreneurship and the added value that co-creation, facilitated by Web 3.0 technologies, can bring to businesses. It delves into the potential advantages of integrating co-creation strategies, such as increased innovation, customer engagement, and market adaptability, while highlighting the role of emerging web technologies in enabling more effective collaboration and interaction between businesses and consumers. The various formations of customer integration in terms of ideational and inventive service and new product development represent an essential factor of economic success in the current work reality for companies. In this emerging epoch, which is constitutively characterized by increasing disruption processes and is referred to by politics and economics etymologically and polysemically as Industry 4.0 and Economy 4.0, a more precise discourse analysis is required in a problem-explorative manner. As a result of an increasingly individualized, informatized, and internationalized society, in which the Java API Web 3.0 not only leads to the transformation of the communication matrix through web-semantic algorithms per se, there is potential added value through co-creation. The customer, in the sense of appropriation research, is not only a profane website visitor but can be determined as an ideational and inventive prosumer with regard to conversion who, within the framework of integrative, interactive, and readaptive value creation, offers companies a decisive benefit reciprocally with the help of Web 3.0. Companies are looking for ways to cope with the phenomenon of ever-shortening product life cycles.